Pengenalan Dasar Dasar Akuntansi dan Akuntansi di Era Digital - Nina Nursida; Raja Ade Fitrasari Mochtar; Yolanda Pratami; Amelia Fitri; Salzabela Ushabina Caramoy; Norhayati Rafida Abdul Rahim; Ihab Ahmed Ra'Uf Awais; Muhammad Raqib Mohd Sofian (2026)
Non-Indexed Publication